If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 + 6r = 3 + 5(6 + 3r) -39 + 6r = 3 + (6 * 5 + 3r * 5) -39 + 6r = 3 + (30 + 15r) Combine like terms: 3 + 30 = 33 -39 + 6r = 33 + 15r Solving -39 + 6r = 33 + 15r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-15r' to each side of the equation. -39 + 6r + -15r = 33 + 15r + -15r Combine like terms: 6r + -15r = -9r -39 + -9r = 33 + 15r + -15r Combine like terms: 15r + -15r = 0 -39 + -9r = 33 + 0 -39 + -9r = 33 Add '39' to each side of the equation. -39 + 39 + -9r = 33 + 39 Combine like terms: -39 + 39 = 0 0 + -9r = 33 + 39 -9r = 33 + 39 Combine like terms: 33 + 39 = 72 -9r = 72 Divide each side by '-9'. r = -8 Simplifying r = -8
| x=1/2(40) | | -5j=250 | | 2(3x-2)-5(x-1)=1(3) | | -t^2-13=0 | | -8b=184 | | x=1/2(66-54) | | x=1/2(66+54) | | 1/4k=3/6k-1/4 | | 28-4n=-4n-7(n+3) | | (2x-1)(3x-1)=(x+1)(4x-2) | | 8x-18=39x+19 | | logx-1(4x-4)=2 | | t^2+13t=0 | | 4e^3x-2=244 | | 7(n+6)=98 | | 2(6x-7)=-39+7x | | 105=-7(x-8) | | -9-4x=-6x-19 | | 0.8x-1.8=3.9x+1.9 | | 6(1-4m)=-90 | | 5(2+2x)=4(3-3x) | | (4n-7)(8n-7)= | | 17=1+4p | | cos(3x+20)=0.2 | | 240=12x | | ab=9 | | 1=4+p | | 8x^2-12y+4=y+10 | | cos(3o+20)=0.2 | | 4+3x+6=4x-5 | | x+(-10)=-22 | | 27-7r=-(1+3r) |